Organizational ethnography and religious organizations: the case of Quaker decision-making. Issue 4 (8th August 2018) - Burton, Nicholas; Koning, Juliette; Muers, Rachel
ABSTRACT: How should we study the management practices of religious organizations to do justice to their distinctive religious motivations and traditions? In this article, we articulate how a specific research approach – organizational ethnography – may enable a deeper understanding of religious and/or spiritual organizational practice. We approach our methodological research questions by engaging with the literature on the distinctive decision-making practices of the Religious Society of Friends (Quakers), commonly known as the Quaker business method. Having shown that the Quaker business method destabilizes a simple binary between "insider" and "outsider" and between believers and nonbelievers, we bring the theory and practice of organizational ethnography into conversation with Quaker accounts of decision-making. We conclude with pathways for future research in the space this destabilization creates.